SPEAK UP: ABRAHAM’S NEGOTIATION WITH GOD AS A TEACHING MOMENT FOR JUSTICE ADVOCACY - Morado, Yuda (Diegesis : Jurnal Teologi, 2025)
This study examines Genesis 18:16-33, focusing on the conversation between God and Abraham regarding the destruction of Sodom and Gomorrah. The study aims to explore how this narrative teaches about divine justice, mercy, and the relational nature of God. Using a qualitative and exegetical approach, the study analyzes the text in its historical and literary context, incorporating secondary theological sources. The finding of this study is that conversation is a paedagogical moment that becomes a foundation for humans to speak up, advocating for justice.